SISO P-ILC Algorithm for Output Data Dropouts and Its Application in Wastewater Biological Treatment Plant - Gu Qun; Hao Xiaohong; Li Zhuoyue; Wang Hua (Institute of Advanced Engineering and Science, 2014)
In order to improve the efficiency of sewage treatment, We construct P-ILC algorithm for output data dropouts.The P-ILC algorithm is used in the aeration tank of oxygen input link, and according to the actual situation, considering the data generating omissions, adjusting the algorithm can completely control the aeration tank of oxygen. After 15 iterations, we can completely control the oxygen in the aeration tank volume. We know more important is this algorithm may at any time according to need of aeration tank of oxygen supplement, when the lack of oxygen, can open the oxygen filling pump, when sufficient oxygen, close the oxygen filling pump, to achieve energy saving goals, ultimately makes the economic benefits to achieve the highest.